Neutron production in neutron-induced reactions at 96 MeV on 56Fe and 208Pb - Sagrado García I. (2017)
Double-differential cross sections for neutron production were measured in 96-MeV neutron-induced reactions at The Svedberg Laboratory in Uppsala, Sweden. Measurements for Fe and Pb targets were performed using two independent setups: DECOI-DEMON, time-of-flight telescope dedicated to the detection of emitted neutrons with energies between a few and 50MeV and CLODIA-SCANDAL device devoted to measuring emitted neutrons with energies above 40MeV. Double-differential cross sections were measured for an angular range between 15 and 98 deg and with low-energy thresholds (≈2 MeV). Angular and energy distributions and total neutron emission cross sections have been obtained from those measurements. Results have been compared with predictions given by different models included in several transport codes (MCNPX, GEANT, TALYS, PHITS, and DYWAN) and with other experimental data (the EXFOR database). © 2011 American Physical Society.